IoT and big data applications in smart cities: recent advances, challenges, and critical issues - Talebkhah, Marieh; Sali, Aduwati; Marjani, Mohsen; Gordan, Meisam; Hashim, Shaiful Jahari; Rokhani, Fakhrul Zaman (Institute of Electrical and Electronics Engineers, 2021)
The notion of smart cities has remained under evolution as its global implementations are challenged by numerous technological, economic, and governmental obstacles. Moreover, the synergy of the Internet of Things (IoT) and big data technologies could result in promising horizons in terms of smart city development which has not been explored yet. Thus, the current research aims to address the essence of smart cities. To this end, first, the concept of smart cities is briefly overviewed; then, their properties and specifications as well as generic architecture, compositions, and real-world implementations are addressed. Furthermore, possible challenges and opportunities in the field of smart cities are described. Numerous issues and challenges such as analytics and using big data in smart cities introduced in this study offers an enhancement in developing applications of the above-mentioned technologies. Hence, this study paves the way for future research on the issues and challenges of big data applications in smart cities.